Ukraine aid: How Europe can replace US support - Giuseppe Irto; Ivan Kharitonov; Taro Nishikawa; Christoph Trebesch (Kiel Institute for the World Economy (IfW Kiel), 2025)
We study how Europe could replace US support for Ukraine both (i) financially, in terms of the fiscal effort required, and (ii) militarily, in terms of weapon production. Financial effort: The financial challenge of replacing US aid is limited. Currently, European governments are spending just 0.1% of their annual GDP on bilateral aid for Ukraine - a minor effort To replace US aid flows and keep total support at the same level: Europe needs to double its yearly support to an average level of 0.21% of GDP. This is less than half of what Denmark and the Baltics are already doing and on a level of what Poland and the Netherlands do. In short: Europe as a whole would need to follow Scandinavia's or Poland's example. In absolute terms (billions of Euro), the biggest European countries and the EU Institutions will be decisive. To replace US aid and get to 0.21% of GDP, Europe as a whole needs to increase its yearly aid flow from currently exteuro44 bn per year to exteuro82 bn per year. The biggest donors for that effort will be the EU institutions (Commission and EIB), who will need to increase their annual support from currently exteuro16 bn to exteuro36 bn per year. Next comes Germany (from currently exteuro6 billion to at least exteuro9 billion per year), then Great Britain (from exteuro5 to exteuro 6.5 bn per year), then France (from currently just exteuro1.5 bn to exteuro6 bn per year), Italy (from currently just exteuro0.8 bn to exteuro4.5 bn) and Spain (from just exteuro0.5 bn to exteuro3 bn per year). All remaining European donors would need to move from exteuro14 bn to exteuro16.5 bn per year. To avoid freeriding, we recommend offering financial incentives to those countries giving aid to Ukraine. Big Ukrainian donors (in % of GDP) could get priority access to any new EU-level defense financing scheme. Large Ukraine aid could also be exempt from EU fiscal rules, or deducted from each nations' contributions to the EU budget. (...)
Keywords: 330; Military aid; Foreign aid; War; Ukraine; Europe; Russia; Arms Trade; United States; US; Geoeconomics; Militärhilfe; Auslandshilfe; Krieg; Ukraine; Europa; Russland; Waffenhandel; Vereinigte Staaten; USA; Geo-Ökonomie